Regulace trhu v oblasti hazardních her - Makovský, Zdeněk (Univerzita Pardubice, 2007)
The article deals with conditions of the Czech lottery market. The revision of present lottery law is necessary. Only gamble level and not technical resources is for lottery sorting important. This is total insert money and maximal loss per hour.

The article deals with conditions of the Czech lottery market. The revision of present lottery law is necessary. Only gamble level and not technical resources is for lottery sorting important. This is total insert money and maximal loss per hour.
Keywords: hazardní hry; regulace trhu; loterie; právní předpisy